(untitled) (Journal of Statistics on Health Decision, 2019)
Background: Better health care leads to an increase in the average life expectancy with an increase in the aging population. This has higher dependency ratios, so this is reflected in the increase in the need for help and continuity of care (INE, 2012; Martins et al, 2016). Family caregivers have an important role, with the provision of most care (Figueiredo, 2007, Melo, Rua, & Santos, 2014). The assumption of this role has associated a set of specific needs and difficulties (Pereira, 2013, Martins et al, 2016). It is relevant to investigate the care processes, as the health of these caregivers will be potentially affected (Petronilho, 2007). A structured and contextualized Intervention Program aimed at the qualification and support of family caregivers is essential for the transition and adequate performance of the functions. Objective: To understand the impact of a Nursing Intervention Program and how it can influence interventions with family caregivers. Methods: An integrative review of the literature was carried out to find out the main needs evidenced by family caregivers. A Delphi technique was used by a group of experts to adapt the Intervention Program, with 93 nursing activities, in the field of emotional and instrumental support. Finally, a pre and post intervention evaluation was carried out with the implementation of the program with 70 family caregivers, with an average of 6 home visits (mean duration: 52 min.) Over 3 months. In the first analysis, a descriptive statistical analysis was performed, with measures of central tendency and dispersion. From the data obtained, a statistical analysis was performed using the statistical program SPSS version 23.0 (Pereira, 2011; Pestana & Gageiro, 2014). Taking into account trend data with normal distribution, we used a parametric statistical analysis. Results: Of the 70 caregivers, 16 (22.9%) were men and 54 (77.1%) were women, with a mean age of 60 years, 48 ​​(68.6%) married, 11 (15.7%) separated, 10 (14.4%) were single and only 1 (1.4%) widow. Most of them were in this role for the first time (67.1%, n = 47) and only 32.9% (n = 23) had already taken care of whom. The main reason for becoming a caregiver was the affective relationship with the dependent family (n = 51; 81.4%), with 67,1% being caregivers for the first time. The vast majority of the people needing care were either spouses (38.6%) or child (35.7%) and 78.6% lived in the same house. As for the occupation, 36 (51.3%) were retired, 17 (24.3%) had a full-time job, 7 (10%) were unemployed and 7 (10%) were domestic. With regard to education, 75.7% had nine years of school (51.4% of them only had four years of school), 18.6% were in the 12th grade and only 2.9% had a college degree. Regarding the time available for care, 40% provided care 12h / day and 22.9% up to 24h / day. On the vast majority of occasions, care is provided without interruption (92.9%). The care provided was of several domains, the main ones being: emotional support (n = 69, 98.6%); regular supervision (n = 69, 98.6%); management of the care process (n = 65, 92.9%); and mobility care (n = 63; 90%). The main difficulties highlighted were: bath (n = 30, 42.9%); (n = 27, 38.6%), mobility and positioning (n = 26, 37.1%), elimination (n = 15, 21.4%), and feed (n = 3, 4.3%). The main needs were: psychoemotional support (n = 26, 37.1%), training (n = 18, 25.7%), financial support (n = 16, 22.9%), information (n=8, 11.4%) and family support (n = 8, 11.4%). With the implementation of the Intervention Program, it was verified that the health of family caregivers presented improvements in several dimensions, more significant in the mental health component. With regard to the manifested overload, there was a decrease, even though the caregivers continued to highlight the implications of the care provided in their personal lives. Conclusions: A Nursing Intervention Program is a facilitator for the transition experienced by caregivers, but also an important instrument of the work developed by nurses. It provides the necessary emotional and instrumental support to improve care delivery. The perception of the obtained results allows the improvement of the Intervention Program implemented and, in addition, realize the importance of the work developed. References Figueiredo, D. (2007). Cuidados Familiares ao Idoso Dependente (Vol. 4). Lisboa: Climepsi Editores. INE - Instituto Nacional de Estatística, I. P. (2012). Censos 2011 Resultados Definitivos - Portugal. (978-989-25-0181-9). Lisboa: Instituto Nacional de Estatística. Martins, T., Araújo, M. d. F., Peixoto, M. J., & Machado, P. P. (2016). A Pessoa Dependente e o Familiar Cuidador (E. S.. E. Porto Ed.). Porto Melo, R., Rua, M., & Santos, C. (2014). Necessidades do cuidador familiar no cuidado à pessoa dependente: uma revisão integrativa da literatura. Revista de Enfermagem Referência, Série IV (2), 143-151. Pereira, Helder Rocha - Subitamente Cuidadores Informais! Dando voz(es) às experiências vividas. Loures: Lusociência, 2013. 978-989-8075-36-9 Pestana, M.H., & Gageiro, J.N. (2014). Análise de Dados para Ciências Sociais – A Complementaridade do SPSS (6ª Edição). Lisboa: Edições Sílabo Petronilho, Fernando Alberto Soares - Preparação do Regresso a Casa. 1ª. Coimbra: Formasau, Formação e Saúde, Lda., 2007. 978-972-8485-91-7